The phenotypic detection of surface antigen of B lymphocytes, MHC I and MHC II by immunohistochemical techniques in the lymph nodes of Bali cattle infected with malignant catarrhal fever - Rini Damayanti (Indonesian Center for Animal Research and Development (ICARD), 1999)
A study on the phenotypic detection of surface antigen of B lymphocytes, MHC I and MHC II in lymph nodes of Bali cattle affected by malignant catarrhal fever (MCF) was conducted by immunohistochemical techniques using avidin-biotin complex peroxidase methods. A number of monoclonal antibodies against surface antigen of B lymphocytes, MHC I and MHC II were used. The results showed that the surface antigens were all detected either in the MCF or in the non-MCF Bali cattle lymph nodes. MHC I were shown predominantly occupied in the lymph nodes of infected cattle. The surface antigen of B cells and MHC II were less found in the infected ones. This indicates that in the immunopathological processes in MCF infected cattle, B cells were not actively involved in producing antibodies, whereas MHC I may contribute the high degree of susceptibility of Bali cattle to MCF. Key words : MCF, B cells, MHC I, MHC II, Bali cattle, immunohistochemical technique